PERANAN INVESTASI DAN TENAGA KERJA TERHADAP OUTPUT SEKTOR INDUSTRI DI PROVINSI SUMATERA UTARA - Julius Sinaga; Azwar Harahap; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Investment and labor force are the factors that contributed on output formation of industri sector with the result that boosts the economic development of a region. This purpuse of this research is to analyse the influence of investment and labor force input to output of industry sector in province of North Sumatera. The results of the analysis shows that estimation model a production function namely Y =5359380,462 + 1,521X1 + 4,716X2. The coefficient of determination (R 2 ) of the dependent variable is able to explain the dependent variables is investment and labor force(72,7%) of the remaining 28,3% is explained by other factors outside the model. Meanwhile, results of the regression partially trialanalysison the tangible standard (α=5 percents) investment has positive and significant influence toward the output of industry sector with coeficient 1,521 and prob t-statistic is 0,002. While the labor force has positive but not significantly influence toward the output of industry sector with coeficient 4,716 and prob. t-statistic is 0,978. Testing as a whole is using the F where F-sums (14,657) > F-table ( 3,41 ), which means variable invesment and labor force together can be influential significantly to the output of industry sector in North Sumatera.Key words: Investment, Labor force, and Output of Industry.